Definitive chemoradiotherapy with carboplatin for squamous cell carcinoma of the head and neck. (8th March 2017) - Nagasaka, Misako; Zaki, Mark; Issa, Majd; Kim, Harold; Abrams, Judith; Sukari, Ammar
Abstract : Objective: Definitive concurrent chemoradiotherapy (CRT) is considered the standard of care for organ preservation and is the only potentially curative therapy for surgically unresectable patients with stage III to IVb locally advanced squamous cell carcinoma of the head and neck. In patients with high risks for adverse events utilizing cisplatin, carboplatin has been empirically substituted. The objective of this study was to estimate the locoregional control rate, progression‐free survival, overall survival, and adverse events in locally advanced squamous cell carcinoma of the head and neck patients treated with CRT utilizing carboplatin. Study Design: A retrospective single‐arm analysis. Methods: Data on consecutive patients who fit the eligibility criteria were collected. Eligible patients were treated with 70 Gy of radiation therapy and at least two cycles of carboplatin (area of curve [AUC] of 5 between January 2007 to December 2013. Results: Fifty‐four patients were identified. Overall locoregional control rate was 50% (95% confidence interval [CI] 37%–63%). Median progression‐free and overall survival were 21 (CI 11–33) and 40 (CI 33–NA) months, respectively. One‐, 3‐, and 5‐year overall survival were 81% (CI 67%–89%), 59% (CI 41%–73%), and 42% (CI 22%–61%), respectively. Stage III/IVa patients (n = 45) had a median survival of 62 (CI 37–NA months) and 3 years of 71% (CI 53%–84%), whereas stage IVb (n = 9) had a median survival of 31 (CI 4–NA) months and none survived to 3 years. Conclusion: Definitive CRT with carboplatin for locally advanced squamous cell carcinoma of the head and neck was well tolerated and demonstrated comparable results to CRT with cisplatin. Level of Evidence: 4. Laryngoscope, 127:2260–2264, 2017